Instalação e avaliação de um sistema de bombeamento d agua com aerogerador eólico de pequeno porte para propriedades rurais, na cidade de Cascavel - PR - Parizotto, Roberson Roberto (2014)
This project aimed to install a water pumping system with wind generator and evaluation of the performance of the same field, considering the availability of wind energy on site. The system was composed of a small wind turbine Horizontal axis Greatwatt the brand mounted on a self-supporting tower and a water pump from SHURflo brand model 8000, it was installed on CASA (Center for Analysis of Alternative Systems) project. Data on the local wind speed, the power generated by the wind turbine and the water flow pumped by the motor pump were collected. With these data it was possible to determine the wind energy in place, the energy generated by the wind turbine, the wind turbine performance and the relationship between energy generated and the pump flow. Thus, by determining the best times of incidence of wind where it was possible to evaluate the best time range for wind power generation and performance of the pump under the action of different levels of wind speed system.